The level of effectiveness of the performance of the heads of physical education departments in the faculties of basic education for their administrative tasks (Journal of the College of Basic Education, 2022)
Chapter One: Introduction and the importance of the researchThis chapter included the introduction, the importance of the research, and dealt with the importance of the role and responsibility of department heads, as well as the importance of department heads who lack leadership skills and administrative expertise that enable them to carry out their administrative and educational tasks with high efficiency.